Hubungan Beban Kerja Mental dengan Kelelahan Kerja dan Stres Kerja pada Pegawai PT X - Marfuah, Nurvita; Sumardiyono, Sumardiyono; Fauzi, Rachmawati Prihatina (Jurnal Kesehatan Masyarakat, 2024)
PT X is a company engaged in the electricity sector whose work is administrative services related to selling and distributing energy. As a form of customer satisfaction, employees must address customer complaints. Demands for completing targets on time and public complaints are getting higher, forcing employees to wok overtime outside of working hours. These demands cause high mental workload. In addition, the disproportionate number of employees and the workload given make employees complain about symptoms of work fatigue and stress. The purpose of this study was to determine the correlation between mental workload with work fatigue and work stress in the PT X. This study is quantitative observasional analytic with a cross sectional apporach with a population of 107 employess of PT X and a sample of 107 employees. The data collection technique is total sampling. Measuring data on mental workload and work stress using a questionnaire and for work fatigue using a reaction timer. The analysis technique used was distributive for univariate analysis and somer’s test for bivariate analysis. The results of the somer'd correlation test showed that there was a significant relationship between mental workload and work fatigue, with a moderate correlation and positive direction (+) (p = 0.000; r = 0.503), and a significant relationship between mental workload and work stress, with a strong correlation and positive direction (+) (p = 0.000; r = 0.622). There is a correlation between mental workload with work fatigue and work stress for employees at PT X. To employess can adjust working hours properly to demands of duties or responbilities ouside of work and employess should use the rest time that has been given properly.